2017
DOI: 10.1111/andr.12448
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Is immunosuppression, induced by neonatal thymectomy, compatible with poor reproductive performance in adult male rats?

Abstract: With increasing knowledge that the immune system has a major impact on reproductive ‎health, the potential for cells arising in organs such as the thymus to alleviate oxidative stress ‎has been revealed. This study addresses the impact of neonatal thymectomy on male ‎reproductive function in pubertal and adult animals. Neonatal Sprague Dawley rats were allotted to four treatments consisting of fully thymectomized, partially thymectomized, intact, and sham-operated rats. Half of the rats in each treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 77 publications
2
22
0
Order By: Relevance
“…Sperm abnormality and viability were measured in duplicate (200 sperm per sample) after eosin-nigrosin staining (20,31). Spermatozoa with protoplasmic droplets, ab-axial tails, malformed heads, double tails, coiled tails, bent tails, and without tail or head were recorded as abnormal under a phase-contrast microscope (Olympus BX41; Olympus Optical Co. Ltd, Japan) (28,57).…”
Section: Sperm Quality Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm abnormality and viability were measured in duplicate (200 sperm per sample) after eosin-nigrosin staining (20,31). Spermatozoa with protoplasmic droplets, ab-axial tails, malformed heads, double tails, coiled tails, bent tails, and without tail or head were recorded as abnormal under a phase-contrast microscope (Olympus BX41; Olympus Optical Co. Ltd, Japan) (28,57).…”
Section: Sperm Quality Evaluationmentioning
confidence: 99%
“…Oxidative stress (OS), mitochondrial impairment, and their subsequent complications seem to play crucial roles in the xenobiotics-induced reprotoxicity and consequent infertility (20,21,(24)(25)(26)(27)(28)(29)(30). High sensitivity to OS, excessive reactive oxygen species (ROS) levels, and thiobarbituric acid reactive substances (TBARS) content could dramatically affect the functions of the reproductive organs (20,21,(26)(27)(28)(29)(30)(31)(32)(33)(34). For instance, oxidative injury and DNA damage studies indicated that high doses of MWCNT could cause DNA damage in murine sperm (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varicocelised rats in MO treatment and placebo groups were gavaged daily with 150 mg/kg of MO or normal saline for 10 weeks (a complete spermatogenesis cycle of rat) (Ommati et al., ) orally following operation.…”
Section: Methodsmentioning
confidence: 99%
“…Pathogenesis of tissue damage following DZN exposure is usually being attributed to oxidative injury [11]. Increasing oxidative stress through mitochondrial dysfunction and immunosuppression can lead to testicular injury and sperm abnormalities [12]. DZN with oxidative stress and generation of free radicals and increment of lipid peroxidation induce DNA fragmentation and apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%